Decrease in transverse strength of heat polymerized acrylic resin plate after immersion in 15% betel leaf extract (Piper betle Linn.): Penurunan kekuatan transversal plat resin akrilik polimerisasi panas setelah perendaman dalam larutan ekstrak daun sirih (Piper betle Linn.) 15% - Sintha Nugrahini; Helena Jelita; Putu Hanny Ardianingsih (Makassar Dental Journal, 2022)
The method of chemically cleaning dentures by immersion in an effervescent denture cleanser solution for a long time can affect the transverse strength. Betel leaf extract can be used as a natural disinfectant because it contains essential oils that are antimi-crobial by denaturing cell proteins. This study was intended to examine the decrease in the transverse strength of heat polymeri-rized acrylic resin plates after immersion in 15% betel leaf extract solution. The posttest only control group design study used a sample of 24 HPAR plates, which were divided into 6 groups. The plates were immersed in distilled water for 72 hours to re-duce the residual monomer, immersed in 15% betel leaf extract solution, the positive control group in Fittydent® and the nega-tive control group in aquadest for 1 and 6 hours. The transverse strength was tested using the Universal Testing Machine and the data were analyzed using the one-way Anova test. The results showed the average transverse strength after immersion for 1 hour in 15% betel leaf extract, Fittydent®, and aquadest, respectively, namely 46.512±10.965 MPa, 72.744±22.395 MPa, and 81.522±28.854 MPa; after soaking for 6 hours, respectively, namely 49.171±14.246 MPa, 73.894±25.844 MPa, and 71.860± 17.553 MPa. The LSD test showed that there was a significant difference in transverse strength (p<0.05). It was concluded that the immersion of the HPAR plate in 15% betel leaf extract solution for 1 hour and 6 hours decreased the transverse strength.